2015
DOI: 10.1109/tbc.2015.2400819
|View full text |Cite
|
Sign up to set email alerts
|

Providing Vehicular Infotainment Service Using VHF/UHF TV Bands via Spatial Spectrum Reuse

Abstract: In this paper, we identify the potential of the television bands to be used for providing vehicular infotainment service. Specifically, content delivery from the roadside unit to vehicular users is conducted by exploiting the spectrum holes, which is also referred to as spatial spectrum reuse. In this manner, the spectrum utilization efficiency is improved and the digital television service is not interfered. We first give a thorough description on such vehicular content delivery network and indicate the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It has been reported that usage of television bands can facilitate better relaying of service. The work carried out by Chen et al [20] has specified that reusing the spatial spectrum can assist in relaying data for infotainment services. However, the only difference it makes with other conventional approach is that-conventional approaches data is restricted to core internet network (i.e.…”
Section: Infotainment System Over Vehicular Networkmentioning
confidence: 99%
“…It has been reported that usage of television bands can facilitate better relaying of service. The work carried out by Chen et al [20] has specified that reusing the spatial spectrum can assist in relaying data for infotainment services. However, the only difference it makes with other conventional approach is that-conventional approaches data is restricted to core internet network (i.e.…”
Section: Infotainment System Over Vehicular Networkmentioning
confidence: 99%
“…The work of Felice et al [24] has presented a design of the infotainment system that uses self-healing mechanism in order to support critical application. Chen et al [25] have used television spectrum bands for relaying services over infotainment system. Luddecke et al [26] have used Bayesian network in order to model an infotainment system.…”
Section: Related Workmentioning
confidence: 99%
“…For the up-to-date research works, in terms of the vehicular content disseminate with the support of white spaces infrastructure, Yu et al [13] studied the bandwidth efficient and rate-adaptive video delivery by using the dynamically sensed TVWS channels. By fully considering the TVWS spatial spectrum reuse, Chen et al [25] introduced a vehicular Infotainment service provisioning approach with the goal of content delivery throughput maximization and spectrum efficiency enhancement. A. Achtzehn et al [26] only considered the delaysensitive emergency safety message (ESM) dissemination by utilizing the TVWS channels.…”
Section: Related Workmentioning
confidence: 99%